Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/myc.12955
|View full text |Cite
|
Sign up to set email alerts
|

The combination of tamoxifen with amphotericin B, but not with fluconazole, has synergistic activity against the majority of clinical isolates of Cryptococcus neoformans

Abstract: Summary Background Cryptococcal meningitis has fatality rates of 40%‐70%, resulting in 200 000 deaths each year. The best outcomes are achieved with amphotericin combined with flucytosine but flucytosine is expensive and unavailable where most disease occurs. More effective and affordable treatments are needed. Tamoxifen, a selective oestrogen receptor modulator frequently indicated for breast cancer, has been found to have synergistic activity against the Cryptococcus neoformans type strain when combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…In this review, we summarized the antifungal effects of a number of non-antifungal agents. In addition, some antitumor agents such as miltefosine (Wu et al 2020 ), tamoxifen (Hai et al 2019 ), methotrexate (Yang et al 2019 ), and antiepileptic drugs (Kathwate et al 2015 ) have been reported to have antifungal effects. The use of drug repurposing strategies in the discovery of novel antifungal agents is a revelation in the identification of new antifungal drugs through structural readjustment.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we summarized the antifungal effects of a number of non-antifungal agents. In addition, some antitumor agents such as miltefosine (Wu et al 2020 ), tamoxifen (Hai et al 2019 ), methotrexate (Yang et al 2019 ), and antiepileptic drugs (Kathwate et al 2015 ) have been reported to have antifungal effects. The use of drug repurposing strategies in the discovery of novel antifungal agents is a revelation in the identification of new antifungal drugs through structural readjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen has in vitro antifungal activity against Cryptococcus spp. clinical isolates, with MIC ranging from 2 to 16 µg/mL, acting synergistically when combined with AMB and FLC [73,74]. In the murine disseminated cryptococcosis model, treatment with tamoxifen at 200 mg/kg/day combined with FLC at 5 mg/kg/day decreased the burden fungal by~1 log in the brain tissue [74].…”
Section: Tamoxifenmentioning
confidence: 99%
“…Sertraline (see also below) reached phase III clinical trials for treatment of cryptococcal meningitis; however, the drug did not demonstrate superiority compared to current treatment options in preventing morbidity and mortality (35,36). Other notable reports on repurposing drugs as antifungals include AR-12, a derivative of celecoxib which demonstrated broad-spectrum antifungal activity (37,38); tamoxifen, an estrogen receptor antagonist used primarily to treat breast cancer (39,40); and derivatives of the antimalarial drug mefloquine (41).…”
Section: Repurposing For the Identification Of Drugs With Novel Antifungal Activitymentioning
confidence: 99%